2018
DOI: 10.1186/s13000-017-0682-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel GLI3 variant causing overlapped Greig cephalopolysyndactyly syndrome (GCPS) and Pallister-Hall syndrome (PHS) phenotype with agenesis of gallbladder and pancreas

Abstract: Background: A proper balance between the activator and the repressor form of GLI3, a zinc-finger transcription factor downstream of hedgehog signaling, is essential for proper development of various organs during development. Mutations in different domains of the GLI3 gene underlie several congenital diseases including Greig cephalopolysyndactyly syndrome (GCPS) and Pallister-Hall syndrome (PHS). Case presentation: Here, we describe the case of an overlapped phenotype of these syndromes with agenesis of the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The green arrow indicates the amplicon of the wild type allele, while the red one indicates the amplicon of the mutated allele. (c) A schematic view of the truncated GLI3 protein and its functional domains (part of the frameshifted sequence of exon 5 has been omitted for clarity): the red square indicates the repressor domain (RD; aa106‐aa263), the blue square indicates the zinc finger domain (ZFN; aa462‐aa645), the gray square indicates the proteolytic cleavage site (PC; aa703‐aa740), and green squares indicate both transactivation domain 2 (TA2; aa1044‐aa1322) and transactivation domain 1 (TA1; 1376‐aa1580; according to Ito et al, )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The green arrow indicates the amplicon of the wild type allele, while the red one indicates the amplicon of the mutated allele. (c) A schematic view of the truncated GLI3 protein and its functional domains (part of the frameshifted sequence of exon 5 has been omitted for clarity): the red square indicates the repressor domain (RD; aa106‐aa263), the blue square indicates the zinc finger domain (ZFN; aa462‐aa645), the gray square indicates the proteolytic cleavage site (PC; aa703‐aa740), and green squares indicate both transactivation domain 2 (TA2; aa1044‐aa1322) and transactivation domain 1 (TA1; 1376‐aa1580; according to Ito et al, )…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatics analysis demonstrated that the alternative splicing is predicted to cause a translational frameshift of 57 amino acids and formation of premature termination codon, thus resulting in truncated protein NP_000159.3:p.(His123Argfs*57). According to the Pfam and UniProt database, truncated GLI3 (UniProtKB: P10071) protein lacks part of its repressor domain (RD; aa106‐aa263), zinc finger domain (ZFN; aa462‐aa645), proteolytic cleavage site (PC; aa703‐aa740), transactivation domain 2 (TA2; aa1044‐aa1322), and transactivation domain 1 (TA1; 1376‐aa1580; Figure c; Ito et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their results combined with previous studies, Shen et al, calculated a 3% probability of BA when non‐visualized GB is confirmed on repeat sonograms . A non‐visualized GB may be associated with multiple congenital anomalies (cardiovascular [58.3%], gastrointestinal/genitourinary [25%], anterior abdominal wall [10.4%], and central nervous system [6.3%]), various genetic syndromes, and intestinal obstruction or agenesis. Fetal chromosomal abnormalities should be suspected in all cases where an absent gallbladder is not the sole US abnormality detected .…”
Section: Absent Gallbladdermentioning
confidence: 99%
“…Together, these studies support the concept that hedgehog and androgen pathways collaborate to orchestrate male sex differentiation and highlight Gli3 in particular as a potentially important intermediary between the two. In humans, there is a subset of male patients with mutations in GLI3, including autosomal dominant GLI3 anomalies categorized as Greig cephalopolysyndactyly syndrome (GCPS) and Pallister-Hall syndrome (PHS), that exhibit differences in male sex differentiation [13,14]. Despite these reports, the role for GLI3 in urogenital development remains unknown.…”
Section: Introductionmentioning
confidence: 99%